Financing the German Mittelstand - Ulrich Hommel; Hilmar Schneider (EIB Papers, 2003)
Based on a survey conducted among German Mittelstand firms and capital structure data on the Mittelstand, this paper sheds light on the current and future financing situation of the Mittelstand. The paper documents the equity shortage and dependence on bank debt typically associated with the Mittelstand. It further emphasises that - at present - fears of systematic credit rationing are difficult to substantiate (though a lack of alternative sources of finance can be expected to adversely affect future credit supply) and argues that the consolidation of the German banking sector as well as Basel II should not constitute major obstacles to the future growth of the Mittelstand. Still, the paper concludes that a typical Mittelstand firm's access to external finance will remain a key factor and, against that background, comments on specific measures of improvement from the perspective of regulators, banks, and firms.
Keywords: 330; Klein- und Mittelunternehmen; Unternehmensfinanzierung; Deutschland